A Tale of Two “Rumah”: State, Market and Two Austronesian Communities - Bien Chiang (International Journal of Environment, Architecture, and Societies, 2021)
In this paper, I will juxtapose the socio-economic histories of two Austronesian communities in order to highlight the working of a key cultural concept, “house” or rumah, in both communities in the face of encroaching contemporary state and market forces. The communities under consideration are an Iban longhouse community of Sarawak and a Paiwan community of Southern Taiwan. Both group honored a kind of precedence in terms of land occupancy and the utilization of natural resources. Both group follow a rather fundamental cognatic principle in kinship recognition, household division and property transmission. While a comprehensive comparison of the two on so complex a subject is apparently way beyond the scope of a conference paper, I choose here to focus on the interplay of state policy (both colonial and independent) and market force on land tenure and land utilization among the two communities, and hope to demonstrate the upholding of the notion umah as a value in these peoples modernization strategies. Even though the contents, scopes and representations of the notion of “House” are different in these two societies, its centralities in their respective social and cultural systems are fascinatingly comparable. I do not intent to say that these two local communities of the Austronesian experience no difficulties whatsoever in their ever-increasing involvement in the national, regional and global systems.  From what we observe, however, we do see that they are not just surviving the encroaching external impacts, they continue to exist as two “rumah”.